Evaluating the Productive Energy Content of High-Protein Distillers Dried Grains in Swine Diets - H. S. Cemin; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband; M. Wilken (Kansas Agricultural Experiment Station Research Reports, 2019)
A total of 300 pigs (DNA 400 × 200), initially 24.5 lb, were used in a study to evaluate the effects of increasing amounts of high-protein distillers dried grains (HP DDG) on growth performance, and to estimate the productive energy of HP DDG. Pens were allocated with 5 pigs each and fed a common diet for 21 d after weaning. Then, pens were assigned to treatments in a randomized complete block design. There were 5 treatments with 12 pen replicates per treatment. Treatments consisted of 0, 10, 20, 30, or 40% HP DDG. Pigs were weighed weekly for 21 d to evaluate average daily gain (ADG), average daily feed intake (ADFI), and feed efficiency (F/G). Caloric efficiency was obtained by multiplying ADFI by kcal of net energy (NE) per lb of diet and dividing by ADG. Productive energy was estimated based on caloric efficiency relative to the diet without HP DDG. Data were analyzed with the GLIMMIX procedure of SAS with block as a random effect and pen as the experimental unit. From d 0 to 7 and 7 to 14, increasing amounts of HP DDG linearly decreased (P<0.01) ADG, which was mainly driven by lower (linear,P<0.01) ADFI. The inclusion of HP DDG negatively impacted (linear;P<0.01) F/G from d 0 to 7 with no evidence for differences from d 7 to 14 (P≥ 0.321). From d 14 to 21, there was a decrease (linear,P<0.01) in ADFI and improvement (linear,P= 0.029) in F/G as HP DDG inclusion increased. Overall (d 0 to 21), pigs fed diets with increasing HP DDG had a linear decrease (P<0.01) in ADG, ADFI, and final body weight. There was a tendency for a quadratic response (P= 0.051) in F/G, with the best F/G observed for pigs fed diets with 40% HP DDG. There was a linear reduction (P<0.01) in caloric efficiency with increasing amounts of HP DDG, indicating an underestimation of HP DDG NE. The productive energy of HP DDG was estimated as 1,218 kcal/lb or 97.3% of corn NE.
Keywords: caloric efficiency; high protein distillers dried grains; growth performance; productive energy